Law and the constitution - Jennings, W. Ivor (London, 1984)
DICKY is reported to have told a Harvard audience, long after the first publication of his Law of the Constitution, that if you scratch an Englishman you will find a socialist. It is doubtful if even a pick-axe would have produced such a discovery in Dicey himself, and what he meant by "socialist " is not what we mean by it now. It is nevertheless true that during the past sixty or seventy years the British Constitution has been pro foundly modified under the influence of collectivist ideas. New institutions have been created, and new powers conferred on existing institutions. This develop ment has been due in part, though in part only, to the extension of the franchise; and the traditional institu tions of democratic and responsible government, such as those of Cabinet, Prime Minister, Parliament, and Civil Service, have had to adapt themselves for the control of greatly extended functions under the ulti mate control of a vast electorate. During the same period the essential ideas on constitutional law and constitutional government have been the subject of close analysis by a long series of brilliant writers, of whom the French appear to me to have contributed most in recent years.
Keywords: Constitution -Great Britain